The Tourist Destination of Constantine and its Relationship to the Capitalist Colonial System : A Reading in the French City Guides - Benderradj, Karima (Journal of Human Sciences, 2022)
This is the second originality of the city as Marc COTE says: one of the most beautiful cities in Algeria; history has combined with the site to make the city.When the French entered Constantine in 1837, they discovered a town perched on a rock isolating the Gorges du Rhummel, and an urban landscape that bears the mark of the fundamental principles of Arab-Muslim urbanism.The interventions on the space were accompanied by the establishment of new institutions supplanting the original organization by the transposition of a new system of administration at the service of the occupants.This essay is an analytical reading of the guides of the city of Constantine established by the French authorities, which show that the city was destined to play a tourist role dictated by a capitalist colonial system that wanted to found a tourist industry by relying on all its potentialities, natural and historical.